The Transformation of Digital Islamic Education at the Global Level and New Directions for 21st-Century Learning - Tamrin Fathoni; Samar A. El-Farra (CV Edujavare Publishing, 2026)
The rapid advancement of digital technologies has transformed educational systems worldwide, including the field of Islamic education. Digital transformation has reshaped teaching and learning processes by integrating online platforms, artificial intelligence, learning management systems, mobile learning, and interactive digital resources into educational practices. This literature review aims to examine the global development of digital Islamic education and explore its implications for twenty-first-century learning. The study employs a literature review approach by analyzing scholarly publications, policy documents, and empirical studies related to digital learning, Islamic education, educational technology, and contemporary pedagogical innovations. The findings indicate that digital Islamic education has expanded learning accessibility, promoted flexible learning environments, facilitated global knowledge exchange, and enhanced learner engagement. However, challenges remain regarding digital literacy, technological infrastructure, educational equity, data privacy, and the preservation of Islamic values within digital environments. The review highlights the importance of integrating technological innovation with Islamic educational principles to create effective, inclusive, and value-oriented learning ecosystems. Future directions emphasize personalized learning, artificial intelligence integration, and the development of sustainable digital educational frameworks that support lifelong learning in Muslim communities worldwide.